A study on the social reproduction conditions of nursing undergraduates of two universities in São Paulo - Celia Maria Sivalli Campos; Vania Ferreira Gomes Dias; Eloá Otrenti; Daniela Miori Pascon; Everson Meireles; Vera Lúcia Mira (SciELO, 2020)
Abstract Objective: To identify the social reproduction characteristics of nursing undergraduates. Method: A quantitative descriptive cross-sectional study conducted in two undergraduate degree courses in nursing, one public and one private, in the state of São Paulo. Results: There were 285 students who participated, with 195 from the public university and 90 from the private one, who answered a questionnaire to classify social reproduction profiles. Four groups with different social conditions were identified. Although most families had stable living conditions, the percentage of families with poor working and living conditions was not negligible. Conclusion: The analysis on the social reproduction of the families of undergraduate students of the two courses exposed stability gradients which are compatible with intermediate social strata.